Beast with five fingers - Bond, Ruskin (New Delhi Rupa publications, 2018)
About ten yards in front of him, crawling along the floor, was a man$1 (Bs hand. Eustace stared at it in utter amazement. It was moving quickly in the manner of a geometer caterpillar, the fingers humped up one moment, flattened out the next; the thumb appeared to give a crablike motion all the while. While he was looking, too surprised to stir, the hand disappeared round the corner.$1 (BTerror lurks where you least expect it!This is a collection of hair-raising horror stories that are bound to make your flesh creep, written by the undisputed masters of the genre. Selected and compiled by Ruskin Bond, these are stories by Rudyard Kipling, W.F. Harvey, Marjorie Bowen and Thomas Burke, among others.From a ghostly animated hand and the walking dead to haunted cemeteries and dressing tables$1 (Bthese tales will send a chill down your spine. Featuring phantoms, beasts and monsters, The Beast with Five Fingers makes for the perfect read when the moon is up!s
Keywords: Fiction